Measuring civic knowledge: using the Delphi method to construct a civic knowledge inventory for elementary teachers - Bietau, Lisa Artman (Kansas State University, 2011)
A foundational mission of our public schools is dedicated to preserving a democratic republic dependent on a literate and actively engaged citizenry. Civic literacy is essential to supporting the rights and responsibilities of all citizens in a democratic society. Civic knowledge is the foundation of our citizens’ civic literacy. National Standards for Civics and Government (Center for Civic Education,1994) promote civic literacy for all students including elementary children. Therefore, understanding important civic concepts is essential knowledge for elementary educators. Civic knowledge has not been required or monitored in teacher preparation or licensure. At the time of this study, there were no comprehensive measures of elementary teachers’ civic knowledge. The purpose of this study was to investigate a project funded by the Center for Civic Education that developed a Civic Knowledge Inventory (CKI) for elementary teachers using a Delphi technique. Specifically, this study analyzed the use of a Delphi process to identify major civic constructs elementary teachers should know and to create a valid and reliable measure of elementary teachers’ knowledge of these selected civic constructs. The Delphi technique engaged eight anonymous civic scholars to work together via the Internet. Through rounds of input and feedback they identified important civic knowledge that elementary teachers should know and created a multiple-choice measurement tool aligned to these constructs. In final analysis, the Delphi panelists collectively created a map of civic concepts that included: Constitutionalism, Representative Democracy, Citizenship, Human Rights, Civic Society, Market Economy and Examples of Non-Democracy as essential constructs accompanied by an outline of related sub-concepts and elements. This outline was then used to design, improve, and ultimately select the best test items for each construct. An item analysis was completed on data produced by 89 volunteer pre-service elementary teachers to identify high performing items to be included in the CKI. Therefore, the CKI could be used to examine the extent to which teacher preparation programs adequately prepare elementary teachers to be civic educators and thus guide teacher preparation as well as related professional development initiatives.
Keywords: Measuring teacher civic knowledge; Civic content knowledge; Elementary civic education; Delphi method; Civic Knowledge Inventory (CKI); Instrument construction; Educational Tests and Measurements (0288); Elementary Education (0524); Social Sciences Education (0534)